National Arabic Test based on Higher Order Thinking Skills - Raswan, Raswan; Wahab, Muhbib Abdul; Busri, Hasan; Siron, Yubaedi (Universitas Islam Negeri Raden Intan Lampung, 2022)
In the 21st century, skills required higher order thinking skills (HOTS). Therefore the test questions developed are directed towards HOTS based. The purpose of this study was to find a HOTS-based Arabic question model in the national level Arabic questions that could be used as a reference for teachers in developing good and appropriate HOTS-based questions and inspirational. The research approach used in this study is a qualitative and quantitative type of research (R&D) research approach. Researchers reveal models of HOTS-based Arabic questions that are in accordance with scientific and modern developments with discussions with Arabic assessment experts, visiting several schools that teach Arabic as a preferred foreign language, discussions with Arabic teachers, interviewing question development officials, and checking national Arabic questions, then discussions with Arabic experts and teachers. The Arabic HOTS question is still understood differently by Arabic teachers and there are still many Arabic questions that have not been categorized as HOTS. Therefore, Arabic teachers need to be given training in developing Arabic HOTS questions but who focus on Arabic questions. So far, the question training is still combined with other materials with speakers who are not experts in developing Arabic questions.